Experimental study of composite cold-formed steel C-section connected back-to-back / Mohamad Rohaidzat Mohamed Rashid , Noorsaidi Mahat & Nazri Nasir - Mohamed Rashid, Mohamad Rohaidzat; Mahat, Noorsaidi; Nasir, Nazri (2009)
Nowadays cold-formed steel sections are widely used in a light-gauge construction that requires a large space. Fast speed erection and light structural weight are the major benefits of using cold-formed steel sections in the construction as they can minimize the equipments demand, thus reducing the cost of construction.Cold-formed steel sections have been utilized and started in the United States for at least a century, but mainly for only non-structural purposes (Hancock et al., 2001). However, as load carrying structural members, the cold-formed steel sections started to become popular in the 20th century especially for use in the industrial and commercial buildings.